2021
DOI: 10.1590/1983-21252021v34n216rc
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICAL AND CHEMICAL DEFENSES OF Cenostigma pyramidale (FABACEAE): A PIONEER SPECIES IN SUCCESSIONAL CAATINGA AREAS

Abstract: Cenostigma pyramidale, a pioneer species presents in all different successional stage (early, intermediate and late) of fifteen natural regeneration areas of Caatinga after land used changed and abandonment was used to investigates the morphological and physiological attributes that are very important to xeromorphic conditions as against herbivories. Leaf samples were collected to evaluate the percentage of the herbivory and index of sclerophylly. Anatomy, histochemistry, total phenolic content, epicuticular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(39 reference statements)
2
5
0
3
Order By: Relevance
“…Limited water availability, as observed during the study period, may thus result in flower and fruit production of plants with ant herbivory not differing from control plants. Although C. pyramidale can tolerate water stress (Ribeiro et al, 2021) and is even recognised as a disturbance‐adapted species (Ribeiro et al, 2015; Ribeiro‐Neto et al, 2016), it has been observed that open and desiccated conditions due to increased aridity combined with human disturbance negatively affect the reproduction of the closely related and co‐occurring species Cenostigma microphyllum (Oliveira et al, 2022). Thus, it seems that even disturbance‐adapted species can have their reproductive success negatively affected in scenarios of very severe environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Limited water availability, as observed during the study period, may thus result in flower and fruit production of plants with ant herbivory not differing from control plants. Although C. pyramidale can tolerate water stress (Ribeiro et al, 2021) and is even recognised as a disturbance‐adapted species (Ribeiro et al, 2015; Ribeiro‐Neto et al, 2016), it has been observed that open and desiccated conditions due to increased aridity combined with human disturbance negatively affect the reproduction of the closely related and co‐occurring species Cenostigma microphyllum (Oliveira et al, 2022). Thus, it seems that even disturbance‐adapted species can have their reproductive success negatively affected in scenarios of very severe environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Presente nos três estádios sucessionais da floresta tropical seca deste estudo e sendo uma espécie de grande importância ecológica (Falcão et al, 2015(Falcão et al, , 2017Ribeiro et al, 2021), a leguminosa Cenostigma pyramidale (Tul.) E. Gagnon & G. P. Lewis foi a planta-modelo para o teste das hipóteses deste estudo, uma vez que apresenta ampla distribuição e estava presente em todos os estádios sucessionais (Cabral et al, 2013).…”
Section: áRea De Estudounclassified
“…As maiores taxas de área foliar registradas em indivíduos presentes no estádio intermediário também foram observadas por Magalhães (2011). No entanto, dois anos depois, após período de seca prolongada, Ribeiro et al (2021) não encontram diferenças significativas nas taxas de herbivoria entre os estádios, provavelmente devido ao aumento da densidade de herbívoros em todos os estádios após chuvas, pela disponibilidade do recurso planta após um período atípico. Segundo Cabral et al ( 2013), a maior abundância de C. pyramidale no estádio intermediário indicam um maior valor de importância desta espécie neste ambiente.…”
Section: Taxas De Herbivoria E Esclerofiliaunclassified
See 1 more Smart Citation
“…Economic growth in the northeastern semi-arid region of Brazil is mainly based on the exploitation of natural resources, which has led to the degradation of ecosystems (GONG et al, 2016). This process is intensified by climate change, which can cause severe damage to plants, especially those related to abiotic stresses, which interfere with plant development (GOMES et al, 2020;RIBEIRO et al, 2021).…”
Section: Introductionmentioning
confidence: 99%